THE ROLE OF DIGITAL DIPLOMACY IN SOCIETY - Sattorov Nazarbek Odiljonovich; Nasirov Lazizkhan Farkhadovich (PEDAGOGS, 2024)
Abstract: Theoretical and practical aspects of digital diplomacy are gaining great importance in modern international relations. The literature presented in this list examines digital diplomacy as a means of increasing effectiveness in the foreign policy of states. Books and studies answer questions about how diplomacy is evolving through the Internet and social media, how it affects relations between nations, new forms of public diplomacy, and the challenges of digital technologies. These works also discuss information security, disinformation, and the role of the human factor in digital diplomacy.The literature is an important guide for international organizations, diplomats, and researchers, providing theoretical and practical recommendations for the effective implementation of digital diplomacy and the development of its analysis.